A Rare Case of Traumatic Internal Mammary Artery Pseudoaneurysm Causing Hemopericardium: Endovascular Management and Literature Review - Devkota, Shritik; Bhandari, Rajan Mani; Sethi, Jasmine; Bhujade, Harish (Acta medica Lituanica, 2025)
Background: Traumatic Internal Mammary Artery (IMA) pseudoaneurysms can be associated with severe complications, including hemopericardium, pericardial tamponade, diaphragmatic paralysis, hemoptysis, and hemorrhagic shock. Early recognition of this rare condition is essential to reduce the risk of significant morbidity and mortality.Case details: We present a case of IMA pseudoaneurysm that was promptly diagnosed by using contrast-enhanced CT and successfully managed with endovascular embolization, leading to the patient’s complete and uneventful recovery.Conclusion: This case emphasizes the importance of early recognition and endovascular management of rare but potentially life-threatening internal mammary artery pseudoaneurysms following thoracic trauma.
Keywords: internal mammary artery pseudoaneurysm; traumatic IMA pseudoaneurysm; endovascular embolization